ANALISIS KASUS ATAS PUTUSAN PENGADILAN AGAMA NOMOR 72/PDT.G/2011/PA-BJI TENTANG PEMBATALAN PENETAPAN PENGADILAN AGAMA NOMOR 8/PDT.P/2010/PA-BJI MENGENAI PENGUASAAN HARTA WARISAN - SRI AYU UTAMI (PREMISE LAW JURNAL, 2016)
Approbative less appropiate religious judge triggers a claim from the third side who feels detrimental because she is more accurate data consequently it should be cancelled with the decision of the Religion Court in Binjai. The research used descriptive analytic and judicial normative method. The solution of the case of possession of inheritance by some of the heirs according to the Islamic Law is appropriate with Article 188 of Islamic Law Compilation where in this research the third side can appeal a legal effort to the authorized court to correct the incorrect determination. The Judge of Religious Court in Binjai can cancel the determination with the decision in the same court, but it is broken the investigation principle on two levels which should be suitable with the Procedure of Civil Law legal effort on determination is a review. The judge’s Consideration on the decision of Religious Court No. 72/Pdt.G/2011/PA. Bji used Article 181 compilation of Islamic Law and Surah An-nisa, 'verse of 176', where in this case the judge is right that the position of SHD is Kalalah. Consequently, the person who has the right to accept SHD’s inheritance is her brothers. However the panel of judges has not stipulated the subtitute heir system where according to the theory, it should be stipulated to determine the heirs. Keywords : Determination of Heirs, Religious Court, Islam Law